2020
DOI: 10.2139/ssrn.3597265
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Roles of High-Speed Train, Air and Coach Services in the Spread of COVID-19 in China

Abstract: To understand the roles of different transport modes in the spread of COVID-19 pandemic across Chinese cities, this paper looks at the factors influencing the number of imported cases from Wuhan and the spread speed and pattern of the pandemic. We find that frequencies of air flights and high-speed train (HST) services out of Wuhan are significantly associated with the number of COVID-19 cases in the destination cities. The presence of an airport or HST station at a city is significantly related to the speed o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
58
1
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(64 citation statements)
references
References 13 publications
2
58
1
3
Order By: Relevance
“…Results show that restrictions on human movement have limited the spread of the virus in China ( Kraemer et al, 2020 ; Tian et al, 2020 ), and the UK ( Hadjidemetriou et al, 2020 ). According to Zhang et al (2020) , the first reaction of many countries/cities to the COVID-19 outbreak was to minimize air travel from/to China, and it had effectively reduced the number of COVID-19 cases imported from China in February 2020. Wu et al (2020) claim that the rapid spread of COVID-19 across China and the globe, in a very short span of time, was attributed to the outbreak during the Chinese New Year, the abundance of connecting flights, and Wuhan's excellent rail connectivity.…”
Section: Resultsmentioning
confidence: 99%
“…Results show that restrictions on human movement have limited the spread of the virus in China ( Kraemer et al, 2020 ; Tian et al, 2020 ), and the UK ( Hadjidemetriou et al, 2020 ). According to Zhang et al (2020) , the first reaction of many countries/cities to the COVID-19 outbreak was to minimize air travel from/to China, and it had effectively reduced the number of COVID-19 cases imported from China in February 2020. Wu et al (2020) claim that the rapid spread of COVID-19 across China and the globe, in a very short span of time, was attributed to the outbreak during the Chinese New Year, the abundance of connecting flights, and Wuhan's excellent rail connectivity.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, some studies focus on the role of mobility in the spread of the viruses ( Pestre, Morel, Encrenaz, & Gagneux-Brunon, 2011 ; Ruan, Wang, & Levin, 2006 ) where they report a positive relationship between mobility and the virus spread. This intuition has been discussed in a recent study conducted in early stages of the COVID-19 pandemic by Zhang, Zhang, & Wang, 2020 , where they found that there is a significant association between the number of COVID-19 positive cases in Chinese cities and the frequency of high speed rail services and flights from Wuhan.…”
Section: Literature Reviewmentioning
confidence: 89%
“…Other studies put an emphasis on the role of multi-modal transportation impacts related to COVID-19, with a focus on China. Zhang et al (2020) examined the factors influencing the number of imported cases, together with the speed and the spread pattern, of the COVID-19 pandemic spread in China, taking into account different modes of transportation (high-speed rails, coach, and air services). They found that the frequencies of high-speed rails and air services out of Wuhan are significantly associated with the number of the COVID-19 reported cases in the destination cities; the presence of high-speed rail stations and airports is also significantly related to the spread speed of the pandemic.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Overall, the focus of our study is on the spatial-temporal evolutionary dynamics of the COVID-19 pandemic on air transportation networks. We do not aim to provide an in-depth analysis of global aviation as a driver in the spread of COVID-19; the reader is referred to other recent studies on this topic (Christidis and Christodoulou 2020;Gilbert and et al 2020;Zhang et al 2020). Our work contributes towards providing a complete picture of the COVID-19 outbreak and its effect on aviation.…”
Section: Introductionmentioning
confidence: 99%